2006
DOI: 10.1111/j.1095-8649.2006.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgically implanted acoustic transmitters >2% of body mass on the swimming performance, survival and growth of juvenile sockeye and Chinook salmon

Abstract: The influence of surgical implantation of an acoustic transmitter on the swimming performance, growth and survival of juvenile sockeye salmon Oncorhynchus nerka and Chinook salmon Oncorhynchus tshawytscha was examined. The transmitter had a mass of 0Á7 g in air while sockeye salmon had a mass of 7Á0-16Á0 g and Chinook salmon had a mass of 6Á7-23Á1 g (a transmitter burden of 4Á5-10Á3% for sockeye salmon and 3Á1-10Á7% for Chinook salmon). Mean critical swimming speeds (U crit ) for Chinook salmon ranged from 47Á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 11 publications
7
95
4
Order By: Relevance
“…The transmitters (48 3 18 mm, 220-mm antenna) weighed 19 g (in air), which represented 0.7-2.4% of the body weight of the 0.8-2.6-kg trout (mean 1.74 kg), a percentage considered to have no effect on fish swimming performance, condition, or growth (Brown et al 1999;Jepsen et al 2002;Brown et al 2006). It is possible that the trout exhibited unnatural behavior for a short period after tagging (e.g., Walker et al 2000), but this would presumably only affect results from the first tracking occasion, which occurred 12 d after the last fish was tagged.…”
Section: Methodsmentioning
confidence: 99%
“…The transmitters (48 3 18 mm, 220-mm antenna) weighed 19 g (in air), which represented 0.7-2.4% of the body weight of the 0.8-2.6-kg trout (mean 1.74 kg), a percentage considered to have no effect on fish swimming performance, condition, or growth (Brown et al 1999;Jepsen et al 2002;Brown et al 2006). It is possible that the trout exhibited unnatural behavior for a short period after tagging (e.g., Walker et al 2000), but this would presumably only affect results from the first tracking occasion, which occurred 12 d after the last fish was tagged.…”
Section: Methodsmentioning
confidence: 99%
“…Although tag burden is a commonly used guide for making inferences regarding tag size appropriateness [8,53,54], length was used as a surrogate for tag burden in this study because measurements of weight were not recorded for PIT fish. This is standard practice when using PIT-tagged fish as controls to minimize handling.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Research has been conducted to evaluate tag effects among many species, transmitter types and sizes, and geographic areas. Specifically, laboratory research has evaluated the survival, growth, tag expulsion, swimming performance, stress levels, and predation of tagged versus untagged fish [4][5][6][7][8][9][10][11]. In these studies, untagged or sham-tagged fish (that is, fish handled in a manner identical to treatment fish, including incisions, but not implanted with a transmitter) typically serve as a comparison to tagged fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some biologists have suggested that this tag burden not exceed 2% (Winter 1996). However, there have been numerous laboratory based studies that indicate that a tag burden higher than this may not influence swimming performance, growth, tag retention, or survival (Brown et al 1999(Brown et al , 2006(Brown et al , 2010Anglea et al 2004;Zale et al 2005). To this day, discussion continues about the 2% rule presented by Winter (1996).…”
Section: Transmitter Size Considerationsmentioning
confidence: 99%